ChemInform Abstract: Copper(I)‐Catalyzed Reductive Cross‐Coupling of N‐Tosylhydrazones with Amides: A Straightforward Method for the Construction of C(sp3)—N Amide Bonds from Aldehydes. Issue 15 (24th March 2016) - Xu, Peng; Han, Fu‐She; Wang, Yan‐Hua
Abstract: An optimized one‐pot sequence A)—B) is developed for a broad spectrum of primary aromatic amides.